Planning and designing of a production facility layout: An efficient framework in a manufacturing process setting - Cheng, Kok Meng; Ramli, Razamin; Ang, Chooi Leng (2010)
Manufacturing companies are continuously evaluating new concepts new concepts and strategies and changing their production systems to gain a competitive edge domestic and global markets. On of the important areas of concern in order to obtain a competitive level of productivity in a manufacturing systems is the layout design and material transportation system (conveyor system). Conveyor systems are used widespread across a range of industries due to their numerous benefits. However, changes in customer's requirements may trigger the need to design other alternatives by re-layout the existing production floor to minimize the space allocation. Hence, this paper discusses effective alternatives of manufacturing process layout. All constraints or criteria involve in the layout problem are identified and described. Subsequently, a framework of an effective and efficient layout design is proposed with the objective to increase the production output and minimize space allocation at the same time. This efficient planning and designing of facility layout in a particular manufacturing setting is expected to minimize material handling cost, minimize overall production time, minimize investment in equipment, and optimize utilization of space.